2020
DOI: 10.1038/s41416-020-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

IDH mutation in glioma: molecular mechanisms and potential therapeutic targets

Abstract: Isocitrate dehydrogenase (IDH) enzymes catalyse the oxidative decarboxylation of isocitrate and therefore play key roles in the Krebs cycle and cellular homoeostasis. Major advances in cancer genetics over the past decade have revealed that the genes encoding IDHs are frequently mutated in a variety of human malignancies, including gliomas, acute myeloid leukaemia, cholangiocarcinoma, chondrosarcoma and thyroid carcinoma. A series of seminal studies further elucidated the biological impact of the IDH mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
284
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(351 citation statements)
references
References 124 publications
3
284
0
2
Order By: Relevance
“…Moreover, studies have shown that IDH1-mutant and wild-type gliomas are different disease entities [ 14 ]. IDH1-mutant glioma grows slower than wild-type glioma and is associated with longer overall survival and progression-free survival and with a better prognosis and survival rate [ 2 9 ]. This prognostic difference has no significant relationship with the grade of the glioma itself [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have shown that IDH1-mutant and wild-type gliomas are different disease entities [ 14 ]. IDH1-mutant glioma grows slower than wild-type glioma and is associated with longer overall survival and progression-free survival and with a better prognosis and survival rate [ 2 9 ]. This prognostic difference has no significant relationship with the grade of the glioma itself [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a large number of studies showed significant differences in prognosis between IDH1-mutant and wild-type gliomas. The prognosis of IDH1-mutant glioma is significantly better than that of wild-type glioma [ 2 9 ]. However, at present, conventional imaging and functional magnetic resonance imaging (such as DWI, ASL, and DCE) could not predict the glioma genotypes before surgery and could not evaluate the glioma genotypes before clinical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4 C, in some cases, short survival is observed at a young age (39-year patient survived only 14 months) and GBM patients with poor prognosis survive more than 2- or 3-years. IDH status is also useful in predicting the OS of patients diagnosed with GBM, and in the selection of appropriate therapeutic strategies [ 40 , 41 ], however, the majority of grade II and III gliomas have a mutant-type of IDH ( Figure 2 ), while survival times vary between these patients ( Figure 4 C). These exceptions appear due to the heterogeneity of gliomas, which hinders the accurate identification of tumor malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Isocitrate dehydrogenase (IDH) enzymes, which contain three isoforms, play key roles in several major cellular metabolic processes, such as the tricarboxylic acid (TCA) cycle, glutamine metabolism, lipogenesis, and redox regulation [ 32 ]. Wild-type IDH1 and 2 localize in the cytoplasm and mitochondria, respectively, and catalyze the decarboxylation of isocitrate to alpha-ketoglutarate (α-KG) with reduction of NADP+ to NADPH [ 33 ].…”
Section: Molecular Pathogenesis Of Gbmmentioning
confidence: 99%